Big Data Analytics and Information Science for Business and Biomedical Applications - Ahmed, S. Ejaz; Nathoo, Farouk (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The analysis of Big Data in biomedical as well as business and financial research has drawn much attention from researchers worldwide. This book provides a platform for the deep discussion of state-of-the-art statistical methods developed for the analysis of Big Data in these areas. Both applied and theoretical contributions are showcased.